(untitled) (International Journal of Engineering and Computer Science, 2017)
The compressed data transmission to be implemented in this work with the help of Fourier series information hiding mechanism. In the proceeding step, the necessity requirement is the problem statement formulation for designing the system. It mainly focuses on the partitions or segmentations of the multimedia content into a compressed one. The compressed content will be hided to be maintained the originality during the data transmission over the network